The Effect Of Good Corporate Governance Implementation Towards Change On Income And Stock Price (A Case Study On Companies Listed In Corporate Governance Perception Index Ranking During 2012-2016) - Kasat, Rimas Nur (Jurnal Ilmiah Mahasiswa FEB, 2017)
The research objective in this paper is to find the effect of Corporate Governance implementation towards income changes and stock price based on Corporate Governance Perception Index from SWA Magazine by using Index Corporate Governance as Independent Variable proxy, the movement of Earning before Tax (EBT) and Closing Price as Dependent Variable proxies. This research was included as quantitative research which used explanatory as a method and regression testing as the evaluation. The researcher used purposive sampling as sampling method by using 13 firms as samples in the period of 2012 to 2016. This study found that Good Corporate Governance implementation effecting stock price. But on the other hand, this study didn’t find any relation between Good Corporate Governance implementation towards income changes. This occurred since the investors or markets, directly give response to stock price rather than to income changes that take longer time. Moreover, Income changes was effected by the other variable was not discussed in this study. Keywords: Good Corporate Governance, Corporate Governance Perception Index, Change on Income, Stock Price